High-sensitive troponin-T in adult congenital heart disease. (1st April 2015) - Eindhoven, Jannet A.; Roos-Hesselink, Jolien W.; van den Bosch, Annemien E.; Kardys, Isabella; Cheng, Jin M.; Veenis, Jesse F.; Cuypers, Judith A.A.E.; Witsenburg, Maarten; van Schaik, Ron H.N.; Boersma, Eric
Abstract: Background: Adult congenital heart disease (ACHD) patients are at risk of late complications including arrhythmias, heart failure and sudden death. High-sensitive troponin-T (hs-TnT) is the standard for diagnosing acute coronary syndrome, but is also associated with cardiac function and prognosis in other cardiac diseases. We aimed to describe hs-TnT level in ACHD patients, and determine its relationship with cardiac function and other biomarkers. Methods: Consecutive ACHD patients, visiting the outpatient clinic, underwent echocardiography, exercise testing and venipuncture on the same day. Results: In total 587 patients were included (median age 33 [IQR 25–41] years, 58% male, 90% NYHA class I). hs-TnT was above the detection limit of 5 ng/L in 241 patients (41%), of whom 47 (8%) had hs-TnT levels above the 99th percentile of normal of 14 ng/L. hs-TnT levels were highest in patients with a systemic RV or pulmonary hypertension. Patients with normal or non-detectable hs-TnT were younger (32 [IQR 24–40] years) than patient with elevated hs-TnT (42 [IQR 36–60] years, p  < 0.001). The prevalence of hs-TnT ≥ 14 ng/L was higher in patients with NYHA ≥ II (36%, p  < 0.001), systemic systolic dysfunction (38%, p  < 0.001), non-sinus rhythm (43%, p  < 0.001) and elevated pulmonary pressures (39%, p  < 0.001). hs-TnT was correlated with NT-proBNP (r = 0.400, p  < 0.001). Conclusions: hs-TnT above the 99th percentile of normal is observed in a non-trivial portion of stable ACHD patients, especially in those with a systemic RV or elevated pulmonary pressures. Since this biomarker of myocardial damage is related to NT-proBNP and ventricular function, its potential predictive value in ACHD patients seems promising and further investigation of underlying mechanisms is warranted.